منتخب معاشی مسائل سے متعلق متجددانہ رجحانات کے نقد وتجزیے کا تحلیلی مطالعہAn Analytical Study of the Critique and Analysis of Modern Trends related to Economic Issues (Al-Qamar, 2020)
This article offers a study of the analysis of modern trends in selected economic issues.  Presenting the arguments of Modernist scholars and their critics, it highlights the accurate position. In this regard, an analytical study of three important issues, including the concept of property, the status of capitalism in Islam, the issue of inheritance of orphaned grandson, has been discussed. It finds that critical analysis of the critics of modernist’s about the issues under discussion is more accurate and more consistent with Islamic teachings.
Keywords: Modern trends; economic issues; critics; analysis